'See you soon?!' Mobility, competition and free-riding in decentralized higher education financing. Issue 4 (3rd April 2021) - Geissler, Matthias; König, Johannes
ABSTRACT: Highly skilled human capital is usually also highly mobile. Concerns regarding interregional migration revolve around suboptimal public financing of higher education rooted in free-riding behaviour if budget responsibilities are decentralized. This investigation sets out to answer whether cross-state mobility of students in general and individual taste variation in the preference for 'home' and 'university' states in particular justify concerns about the free-riding behaviour of state governments. We analyse graduates' location choices when leaving university using a mixed logit model and subsequently relate the revealed taste variation to individual characteristics. The results suggest some attachment to 'home' states that justify concerns about potential free-riding. However, substantial taste variation exists and is partly associated with the quality of human capital. State governments free-riding on the investment of others therefore may face a quality trade-off.